Revision of the Nearctic species of Callomyia Meigen (Diptera: Platypezidae) and phylogeny of the genus - Cumming, Heather J.; Wheeler, Terry A. (Zootaxa, 2016)
The Nearctic fauna of the genus Callomyia Meigen is revised and a phylogeny of the world species, based on morphological characters, is presented. Although morphological data are used primarily to delimit species, molecular sequence data (DNA barcodes) are used where possible, to help determine species boundaries and associate sexes. Species descriptions, diagnoses, and distribution maps are presented, along with illustrations of habitus, male terminalia, and additional important diagnostic characters. A key to the Nearctic species is provided. Ten species are recorded from the Nearctic Region including three new species: C. argentea Cumming sp. nov., C. arnaudi Cumming sp. nov., C. bertae Kessel, C. browni Cumming sp. nov., C. calla Kessel, C. corvina Kessel, C. gilloglyorum Kessel, C. proxima Johnson, C. velutina Johnson, and C. venusta Snow. The female of C. velutina is described, and three new synonyms are proposed: C. cleta Kessel is a junior synonym of C. calla syn. nov.; C. clara Kessel is a junior synonym of C. corvina syn. nov.; and C. liardia Kessel & Buegler is a junior synonym of C. proxima syn. nov. Phylogenetic relationships within the genus are reconstructed. The genus is monophyletic based primarily on the setulose R1 wing vein, female antennal size and three larval characters. The Nearctic species do not form a monophyletic group with respect to the Old World species.